Survival of Sweet Potatoes (Ipomoea batatas L.) Meristems After Cryopreservation by Vitrification - Mozgovska, Anna V.; Shevchenko, Nadiya O.; ÐœÑ–roshnychenkÐ¾, Tatiana M.; Ivchenko, Tatiana V.; Bashtan, Nataliya Ðž.; Vytsenya, Tamara I. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 157.